Determinação de promotores de crescimento em urina e soro de bovinos: validação de um método empregando QuEChERS e UHPLC-HRMS/MS e estudo in vivo - Mariana Cristina da Silva (2022)
This work presents the development and validation of a multi-residue method using QuEChERS and UHPLC-HRMS/MS, to determine 37 growth promoters in bovine urine and 20 in bovine serum. The chromatographic method has been optimized aiming for the separation of the pair of isomers: alpha-trenbolone and beta-trenbolone; methenolone and methyl-testosterone; alpha-zearalenol and zearalenone, which exhibited similar retention times. The spectrometric optimization aimed to obtain a method that reached the quantitative criteria with high sensitivity, thus, the electrospray ion source and fullscan-parallel reaction monitoring were used. As for the extraction procedure optimization, the solvent composition and volume, the types of salts and adsorbents used in the partition and clean-up stages, and the influence of the TRIS solution (pH 9.5) on the extraction of the analytes were evaluated. The optimized condition for extraction of 5 mL of urine consisted of: the addition of TRIS solution (pH 9.5) after the enzymatic hydrolysis step, 10 mL of acetonitrile to extraction, 2 g of NaCl to improve the partition, and 3 g of MgSO4: PSA (2:1, m/m) to clean-up. During validation, the obtained recoveries varied between 84 – 113%, relative standard deviation between 2 and 32%, and quantification limit between 0.2 – 2.5 µg L-1. The developed method was submitted to the Progetto Trieste proficiency test, which proved to be proficient in the analysis of the evaluated anabolic steroids since there were no false positive results in the analysis of methyltestosterone, stanozolol, and β-boldenone. The recoveries for the following analytes also exhibited excellent performance: β-trembolone (R=86%), zeranol (R=90%), and taleranol (R=108%). In the extension of scope to the bovine serum matrix, the method presented adequate performance, with recoveries between 91.1 - 114.1% and a relative standard deviation between 0.3 - 4.0%. The in vivo study, with intramuscular administration of stanozolol in bovines, showed that the metabolite 16-hydroxy-stanozolol is the marker compound in the detection of stanozolol in the urine matrix, with a detection window of 7 to 17 days. In the serum matrix, the stanozolol itself is the most intense compound, with a detection window of 3 to 10 days. In the stability studies, in both matrices, the samples were shown to be stable for 240 days at -20 °C and after 5 freeze/thaw cycles.